The Future of Microbiome‐Based Therapeutics in Clinical Applications. Issue 1 (15th November 2019) - Sharma, Anukriti; Das, Promi; Buschmann, Mary; Gilbert, Jack A.
Abstract : The microbiome, a collection of microorganisms, their genomes, and the surrounding environmental conditions, is akin to a human organ, and knowledge is emerging on its role in human health and diseases. The influence of the microbiome in drug response has only been investigated in detail for the last 10 years. The human microbiome is a complex and highly dynamic system, which varies dramatically between individuals, yet there exists a common core microbiome that is heritable and can be transmitted to progeny. Here, we review the role of the human microbiome, which is now widely accepted as a major factor that drives the interpersonal variation in therapeutic response. We describe examples in which the microbiome modifies drug action. Despite its complexity, the microbiome can be readily altered, with the potential to increase the benefits and reduce the toxicity and side effects associated with pharmaceutical drugs. The potential of new microbiome‐based strategies, such as fecal microbiota transplant, probiotics, and phage therapy, as promising medical therapeutics are outlined. We also suggest a combination reductionist and system‐level approaches that could be applied to further investigate the role of microbiota in drug metabolism modulation of drug response. Finally, we emphasize the importance of combining microbiome and pharmacology studies as a novel means to treat disease and reduce side effects.